Clinical Supervision with Lesson Study to Improve the Performance of Elementary School Teachers - Alfiah, Alfitriatun Nurun; Harris, Taufiq; Wahyudi, M. Furqon (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The performance of elementary school teachers is a key factor in determining the quality of learning. However, the practice of academic supervision in schools is still largely administrative and has not fully functioned as reflective professional development. This study aims to analyze the implementation of clinical supervision with a lesson study approach to improve the performance of elementary school teachers and to understand the meaning of teachers’ reflective experiences during the supervision process. This research uses a qualitative approach with a case study design. The research subjects include the principal and elementary school teachers directly involved in clinical supervision based on lesson study. Data were collected through in-depth interviews, classroom observations, and document studies, then analyzed using the interactive model of Miles, Huberman, and Saldana through the stages of data reduction, data presentation, and conclusion drawing, with triangulation to maintain data validity. The results of the study show that clinical supervision with lesson study was carried out collaboratively through the stages of planning, implementation, and joint reflection. The reflection process encouraged teachers to critically recognize the strengths and weaknesses of their teaching practices. Changes in teacher performance were not only demonstrated by improvements in lesson planning and teaching strategies but also by the development of reflective awareness and professional commitment. This study concludes that the integration of clinical supervision and lesson study is an effective strategy for sustainable professional development of teachers. The novelty of this study lies in revealing the meaning of teacher reflection as the core of performance change in clinical supervision based on lesson study.